Penerapan Senam Kaki Diabetik Terhadap Tingkat Resiko Terjadinya ULKUS Diabetik Pada Penderita Diabetes Mellitus di Wilayah Kerja Puskesmas Sukoharjo - Kurnia Jelly; Ika Silivitasari (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Diabetes mellitus is a chronic disease of insulin metabolism which is characterized by glucose levels exceeding normal values. Diabetic ulcers are one of the causes of the risk of infection if not treated properly and correctly. Factors that cause diabetic ulcers are poor blood circulation, age, gender, lack of physical activity, and an increase in diabetes mellitus. This application aims to determine the effect of foot exercises on the risk level of diabetic ulcers in people with diabetes mellitus. Descriptive by conducting an application to 2 respondents 3 times in 1 week with an interval of 2 days. Respondents measured the highest systolic blood pressure between the right and left brachials and the right and left ankles which was then divided to obtain the Ankle Brachial Index (ABI) value before and after carrying out diabetic foot exercises. After implementing it 3 times, the result was that the ABI value for both respondents increased, namely by the difference between Mrs. Sa 0.25 mmHg and Mrs. Si 0.30 mmHg. It was found that there was an increase in the Ankle Brachial Index (ABI) value before and after carrying out diabetic foot exercises in both respondents.